The Analysis of Moral Values in the Novel “the Midnight Library” - Jufiati, Jufiati (English Literature Studi Program Universitas Islam Makassar, 2024)
The study aims to find out how the main character reflects on himself and to find out people’s attitudes towards the main character in the novel “The Midnight library” The analysis of moral value in novel ‘The midnight library. The analysis used is the method of analysis data. The data in this research are words that contain moral values in the novel